(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
The African Court on Human and Peoples’ Rights (African Court) handed down its first judgment on the right not to be arbitrarily deprived of one’s nationality in relation to the right not to be arbitrarily expelled in the case of Anudo OchiengAnudo v Tanzania. The Court was seized by Anudo Ochieng Anudo, a Tanzanian national. In its judgment, the African Court relied on Article 15(2) of the Universal Declaration of Human Rights to find against the respondent State. The position of theCourt is contrary to a consistent position of the African Commission on Human and Peoples’ Rights (African Commission) in similar cases. This commentary therefore aims to highlight the particularity of this judgment in relation to the jurisprudence ofthe African Commission and European courts. It emphasises the need to finalise the adoption of the Protocol to the African Charter on Human and Peoples’ Rights on the Specific Aspects of the Right to Nationality and the Eradication of Statelessness in Africa for effective protection of this right in Africa